Analisis Pengelolaan Sampah Pada Masyarakat Medan Krio Kecamatan Sunggal Kabupaten Deli Serdang - Tamaulina Br.Sembiring; Khanif Amar Lubis (Global Leadership Organizational Research in Management, 2024)
In daily life, waste is something that is always there. Finding out about the current waste management system in Medan Krio, Sunggal subdistrict, and Deli Serdang district is the goal of this study. Qualitative research using a descriptive observational design is the methodology employed. The study employed various research techniques, including field surveys, participant-led focus groups, open interviews, and literature reviews. Representatives from the Environmental Agency, village heads, village representative bodies, youth organizations, and village organizations were among the participants in this study. The study's findings indicate that the village's waste management is still inadequate. This is because there isn't enough land to erect temporary shelters, the infrastructure and facilities are still subpar, and there is still a low level of public awareness of the significance of proper waste management. A budget for the purchase of land that will be used for temporary housing should be included, along with recommendations for routine village clean-up schedules and socialization about proper and ethical waste management.